DOES THE GREAT VALLEY GROUP CONTAIN JURASSIC STRATA? REEVALUATION OF THE AGE AND EARLY EVOLUTION OF A CLASSIC FOREARC BASIN - Surpless K.D.; Graham S.A.; Covault J.A.; Wooden J.L. (My University, 2006)
The presence of Cretaceous detrital zircon in Upper Jurassic strata of the Great Valley Group may require revision of the lower Great Valley Group chronostratigraphy, with significant implications for the Late Jurassic-Cretaceous evolution of the continental margin. Samples (n = 7) collected from 100 km along strike in the purported Tithonian strata of the Great Valley Group contain 20 Cretaceous detrital zircon grains, based on sensitive high-resolution ion microprobe age determinations. These results suggest that Great Valley Group deposition was largely Cretaceous, creating a discrepancy between biostratigraphy based on Buchia zones and chronostratigraphy based on radiometric age dates. These results extend the duration of the Great Valley Group basal unconformity, providing temporal separation between Great Valley forearc deposition and creation of the Coast Range Ophiolite. If Great Valley forearc deposition began in Cretaceous time, then sediment by passed the developing forearc in the Late Jurassic, or the Franciscan subduction system did not fully develop until Cretaceous time. In addition to these constraints on the timing of deposition, pre-Mesozoic detrital zircon age signatures indicate that the Great Valley Group was linked to North America from its inception. © 2006 Geological Society of America.
Keywords: BIOSTRATIGRAPHY; BUCHIA; DETRITAL ZIRCON; GREAT VALLEY; JURASSIC; Mesozoic::Jurassic; Мезозой::Юрская